2006
DOI: 10.1097/01.shk.0000209557.31457.ae
|View full text |Cite
|
Sign up to set email alerts
|

Intraluminal Pancreatic Serine Protease Activity, Mucosal Permeability, and Shock

Abstract: Shock states are characterized by a pronounced activation of numerous cell types that lead to an acute inflammatory reaction. The exact mechanism by which these inflammatory cells are activated is not known. Numerous studies have implicated the gastrointestinal tract as one of the main sites for the generation of inflammatory mediators and initiation of an acute systemic response. The pancreas is known to secrete powerful digestive enzymes, and we hypothesize that they may play a leading role in the pathogenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…Thus our studies showing that LDL protects against T/HS-induced myocardial dysfunction is consistent with the notion that gut-derived myocardial depressant factors are involved in acute postshock myocardial dysfunction syndromes. These results also support a recent study in dogs showing that ligation of the cisterna chylae protected against the development of myocardial dysfunction after superior mesenteric artery occlusion (8) as well as studies from the laboratory of Schmid-Schönbein implicating the action of pancreatic enzymes on the ischemic gut as the genesis of factors leading to shock and cardiac dysfunction (1).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Thus our studies showing that LDL protects against T/HS-induced myocardial dysfunction is consistent with the notion that gut-derived myocardial depressant factors are involved in acute postshock myocardial dysfunction syndromes. These results also support a recent study in dogs showing that ligation of the cisterna chylae protected against the development of myocardial dysfunction after superior mesenteric artery occlusion (8) as well as studies from the laboratory of Schmid-Schönbein implicating the action of pancreatic enzymes on the ischemic gut as the genesis of factors leading to shock and cardiac dysfunction (1).…”
Section: Discussionsupporting
confidence: 77%
“…In fact, Cox et al (8) recently reported that an isolated episode of intestinal ischemia will lead to myocardial dysfunction in dogs and that this gut-induced effect also appears to be transduced via the intestinal lymphatics. The mechanisms by which these lymphatic borne factors are produced as well as the organs involved in their production seem to involve pancreatic enzymes interacting with the ischemic gut (1,14,28). Furthermore, our recent studies measuring cardiac contractility in isolated hearts and myocytes from rats subjected to burn injury (20,32) have shown that mesenteric lymph generated following burn injury directly causes changes in cardiac contractility, thereby supporting the role of mesenteric lymph as a key factor involved in regulating myocardial contractile dysfunction.…”
mentioning
confidence: 87%
“…Several studies have demonstrated that inhibition of intraluminal pancreatic enzymes during the resuscitation minimizes the acute inflammatory response as well as histological organ injury (9, 26, 27). In addition, on ligating the pancreatic duct several weeks before hemorrhage, delayed mucosal injury and prolonged survival has been observed (11, 13).…”
Section: Discussionmentioning
confidence: 99%
“…a breakdown of a variety of autologous molecules by one's own digestive enzymes. So far, the evidence supporting this hypothesis is derived from preclinical studies [53]. The evidence in man is still missing but the idea will spark clinical studies.…”
Section: Discussionmentioning
confidence: 99%